Sa12b Improves Biological Activity of Human Degenerative Nucleus Pulposus Mesenchymal Stem Cells in a Severe Acid Environment by Inhibiting Acid-Sensitive Ion Channels - Wang, Ziyu; Han, Letian; Chen, Haoyu; Zhang, Shengquan; Zhang, Sumei; Zhang, Hua; Li, Yuhao; Tao, Hui; Li, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Sa12b is a wasp peptide that can inhibit acid-sensitive ion channels (ASICs). The biological effects of nucleus pulposus mesenchymal stem cells (NP-MSCs) have not been investigated. Therefore, this study investigated the effect of Sa12b on the biological activity of NP-MSCs through ASICs in the acidic environment of intervertebral disc degeneration (IVDD). In this study, NP-MSCs were isolated from the nucleus pulposus (NP) in patients who underwent lumbar disc herniation surgery, identified by flow cytometry and tertiary differentiation, and cultured in vitro in an acidic environment model of IVDD with a pH of 6.2. Proliferation, and apoptosis were observed after different Sa12b concentrations were added to P2 generation NP-MSCs. The Ca2+ influx was detected using flow cytometry and laser confocal scanning microscopy, and qPCR was used to detect the relative expression of stem cell–associated genes (Oct4, Nanog, Jag1, and Notch1), the relative expression of extracellular matrix (ECM)–associated genes (collagen II, aggrecan, and SOX-9), and the relative expression of genes encoding ASICs (ASIC1, ASIC2, ASIC3, and ASIC4). Western blotting was used to detect the protein expression of collagen II and aggrecan in different treatment groups. Cells isolated and cultured from normal NP were spindle-shaped and adherent, and they exhibited expansion in vitro. Flow cytometry results showed that the cells exhibited high expression of CD73 (98.1%), CD90 (97.5%), and CD105 (98.3%) and low expression of HLA-DR (0.93%), CD34 (2.63%), and CD45 (0.33%). The cells differentiated into osteoblasts, adipocytes, and chondrocytes. According to the International Society for Cellular Therapy criteria, the isolated and cultured cells were NP-MSCs. With an increase in Sa12b concentration, the cell proliferation rate of NP-MSCs increased, and the apoptosis rate decreased significantly, reaching the optimal level when the concentration of Sa12b was 8 μg/μl. When the Sa12b concentration was 8 μg/μl and contained the ASIC non-specific inhibitor amiloride, the Ca2+ influx was the lowest, followed by that when the Sa12b concentration was 8 μg/μl. The Ca2+ influx was the highest in the untreated control group. qPCR results showed that as the concentration of Sa12b increased, the relative expression of Oct4, Nanog, Jag1, Notch1, collagen II, aggrecan, and SOX-9 increased, while that of ASIC1, ASIC2, ASIC3, and ASIC4 decreased. The difference was statistically significant (p < 0.05). In conclusion, Sa12b can improve the biological activity of NP-MSCs in severely acidic environments of the intervertebral disc by reducing Ca2+ influx via AISC inhibition and, probably, the Notch signaling pathway. This study provides a new approach for the biological treatment of IVDD. Inhibition of AISCs by Sa12b may delay IVDD and improve low back pain.